IMPROVING THE SCIENCE LEARNING OUTCOMES OF CLASS VIII STUDENTS THROUGH THE JIGSAW-TYPE COOPERATIVE LEARNING MODEL ASSISTED WITH IMAGE MEDIA AT SMP NEGERI SATAP PRAIMARADA - Meici Gralia Talia Rohi; Yohana Makaborang; Yohana Njoeroemana (Universitas Bhinneka PGRI, 2023)
The research was conducted with the aim of knowing student activity and learning outcomes using the Jigsaw type cooperative learning model on the respiratory system material in humans at SMP Negeri Satap Praimarada. This research is a Classroom Action Research (CAR) which consists of pre-cycle activities, cycle 1, and cycle 2, with a total of 30 students. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. Number of students who are inactive 3 people with a percentage of 13.33%. outcomes with an average of 57.3% total students who completed 4 with a percentage of 13,3% and 26 students who did not complete with a percentage of 86,67%. Furthermore, in cycle 1, student activities which consist of affective aspects, there are 12 students with good predicate and 18 students with sufficient predicate. Then the learning outcomes in cycle 1 the average value of all students who completed 73.2 students consisted of 13 people with a percentage of 43.3% who did not complete consisting of 17 people with a percentage of 56.6%. In cycle 2 student learning outcomes there are 16 students with very good predicate and 14 students with good predicate. Learning outcomes in cycle 2, the average value of all students was 81.5 students who completed consisted of 25 students with a percentage of 83.3% and students who did not complete consisted of 5 students with a percentage of 16.6%. Thus, it can be concluded that the application of the jigsaw type cooperative learning model to the learning outcomes of Biology on the respiratory system material in class VIII-IPA humans at SMP Negeri Satap Praimarada.